Rancangan Dan Aplikasi Sistem Keamanan Kendaraan Bermotor Menggunakan Mikrokontroler Dan GPS Modul Dengan Metode Prototyping Berbasis Android - Yonathan; Indra Cahya Firdaus (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Currently, the number of motor vehicle theft cases is still quite high, this happens because of the inadequate security system on vehicles produced by manufacturers, where security systems are generally limited to alarms and handlebar locks that can be outsmarted by criminals. With these security tools, vehicles that have been taken by criminals are difficult to find again. To overcome this problem, a "Design and application of a motor vehicle security system using a microcontroller and GPS module with an android-based prototyping method" was created, with the hope that it can help prevent theft and recover vehicles that have been stolen. The method used in this study is prototyping, the purpose of using this method is to perfect the prototype model in order to accept changes in order to perfect the prototype that has been made into a final system. The test was carried out using the black box testing method which focuses on testing the functionality of the application and vehicle safety tools, the results of the system tests carried out obtained the system to function as expected, the tool functions to receive and carry out tasks sent from the android application, and the application successfully displays coordinate data in real time. The result of the research that has been carried out is, the production of a motor vehicle security device, using an ESP32 microcontroller and GPS module, which can send vehicle coordinates in real time through the MQTT protocol, this tool can be controlled remotely using an application that can be run on an Android smartphone. In conclusion from the test results conducted by researchers, this tool works well and is able to provide real-time vehicle location coordinates, so that it can overcome the problem of vehicle loss experienced by motor vehicle users.